2016
DOI: 10.3233/cbm-160580
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of serum LDH in small cell lung cancer: A systematic review with meta-analysis

Abstract: The study suggests significant correlations between elevated serum LDH levels and poor overall survival in patients with SCLC. And serum LDH levels can be measured combining with other tools for assessing the risk stratification and prognosis of SCLC, which shows directions for treatments of SCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
78
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(87 citation statements)
references
References 40 publications
6
78
3
Order By: Relevance
“…As an important prognostic factor for SCLC patients, many researches have revealed the association between elevated LDH levels at baseline and poor survival (9,12). In the present study, patients who had an abnormally elevated baseline LDH were observed to have a 1.92-fold risk of death than those with normal LDH (95% CI, 1.29-2.86).…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…As an important prognostic factor for SCLC patients, many researches have revealed the association between elevated LDH levels at baseline and poor survival (9,12). In the present study, patients who had an abnormally elevated baseline LDH were observed to have a 1.92-fold risk of death than those with normal LDH (95% CI, 1.29-2.86).…”
Section: Discussionmentioning
confidence: 48%
“…Therefore, measurements of serum LDH levels can reflect the intensity of tumor activities and thus can be used as a prognostic biomarker. Zhang et al (9) conducted a metaanalysis involving 4,785 SCLC patients from 28 studies to investigate the prognostic value of baseline LDH for SCLC patients. Their results indicated that patients with an abnormal elevation of serum LDH at baseline would have a 1.45 times higher risk of death than those with normal LDH level (HR =1.45; 95% confidence interval (CI), 1.27-1.66).…”
Section: Original Articlementioning
confidence: 99%
“…These conditions (high consumption of glucose and hypoxic environment) lead to higher LDH levels. More generally, a high LDH level is known to be a factor of poor prognosis in other cancers, such as lung15 and breast cancer16, and two other studies in NEC (pulmonary17 and colorectal12) also reported high LDH serum levels. Among 61 patients with available AST data at diagnosis, 31% had AST ≥ 2 ULN and they were associated with poorer outcome in multivariate analysis.…”
Section: Discussionmentioning
confidence: 91%
“…Several studies have already identified pretherapeutic prognostic markers and scores to predict outcome in SCLC patients [7,8,9,10,11,12,13,14]. A recent study also demonstrated that pretreatment mGPS and PNI are independent predictors of OS in patients with advanced SCLC [14].…”
Section: Discussionmentioning
confidence: 99%
“…For about 30 years, lactate dehydrogenase (LDH) and serum albumin have been described to predict OS in SCLC [7,8,9]. Different markers and scores for acute inflammation, i.e., the neutrophil-to-lymphocyte ratio (NLR), C-reactive protein (CRP) levels, the modified Glasgow prognostic score (mGPS), the prognostic nutritional index (PNI), and the systemic immune-inflammation index (SII) have been associated with poor outcome in SCLC [10,11,12,13,14].…”
Section: Introductionmentioning
confidence: 99%